Antifouling Membrane Modification for Water Desalination: Study of Synthesis and Modification - Muhammad Nur Alam (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
One of the most important ingredients on earth that everyone needs is water. Consumption of large amounts of water is needed in various human activities such as agriculture, power generation, sanitation, drinking water needs and others. Membrane technology has developed into an indispensable platform technology for water purification, including seawater and brackish water desalination, due to its energy-saving and cost-effective qualities. However, membrane fouling, which results from the non-specific interaction between the membrane surface and foulants, severely impedes the effective deployment of membrane technology. Therefore, this review aims to provide a complete overview of the fabrication and modification of polymer or biopolymer based membranes as an antifouling membrane that focused on the method and performance of antifouling membrane, including water flux, salt rejection, and fouling properties. This review will first outline the main foulants and the primary mechanisms of membrane fouling, followed by a discussion of the development of antifouling membranes, including antifouling tactics and preparation methods. In the final site, the author will be show about the application, challenges and potential future of the antifouling membrane for water desalination.